2020
DOI: 10.1039/d0em00075b
|View full text |Cite
|
Sign up to set email alerts
|

Using low cost open-face passive samplers to sample PM concentration and elemental composition in childcare facilities

Abstract: Effective, low noise and low-cost samplers for airborne particulate matter (PM) in indoor environments are needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…Others: ̴ 0.11% In comparison, the total carbon percentage of ambient PM under normal conditions has been reported in other urban regions to be 12-18% [56], while the elemental analysis of PM sampled during non-fire season in the San Francisco Bay Area showed that it was 14% [43]. The higher carbon content of 38.76% detected in the wildfire PM during the Camp Fire period likely indicates enhanced incomplete combustion products.…”
Section: Pm Morphology and Elemental Profilesmentioning
confidence: 90%
See 3 more Smart Citations
“…Others: ̴ 0.11% In comparison, the total carbon percentage of ambient PM under normal conditions has been reported in other urban regions to be 12-18% [56], while the elemental analysis of PM sampled during non-fire season in the San Francisco Bay Area showed that it was 14% [43]. The higher carbon content of 38.76% detected in the wildfire PM during the Camp Fire period likely indicates enhanced incomplete combustion products.…”
Section: Pm Morphology and Elemental Profilesmentioning
confidence: 90%
“…14% [43]. The higher carbon content of 38.76% detected in the wildfire PM during the Camp Fire period likely indicates enhanced incomplete combustion products.…”
Section: Black Carbon Enrichment During the Wildfire Episodementioning
confidence: 91%
See 2 more Smart Citations
“…However, such detailed information can be difficult to ascertain when PM exposure assessment methods are difficult to implement, expensive, or limited to mass concentration data only. Passive PM sampling has been shown to be a convenient, unobtrusive, and relatively low-cost method to conduct community indoor and outdoor air quality studies [8][9][10]. Passive PM samples can be particularly informative when analyzed via scanning electron microscopy plus energy-dispersive X-ray spectroscopy (SEM-EDS).…”
Section: Sampling Methodsmentioning
confidence: 99%